Finite Automata as an Information Model for Manufacturing Execution System and Supervisory Control Integration - Lopes, Yuri Kaszubowski; Rosso, Roberto S.U.; Leal, André B.; Harbs, Eduardo; Hounsell, Marcelo da S. (IFAC Proceedings Volumes, 2012)
The use of MES (Manufacturing Execution System) is an alternative to link the ERP (Enterprise Resource Planning) to the activities at the shop floor. Due to the difference between the transactional feature of the ERP systems and the real-time features of the operations of the shop floor, MES becomes an important tool. SCADA (Supervisory Control And Data Acquisition) are responsible for monitoring the behaviour of shop floor and can interfere or alert in case of failures. The SCT (Supervisory Control Theory) is a formal methodology for modelling and control synthesis of DES (Discrete Event Systems). SCT appears to be an appropriate tool for this task, ensuring an optimal control logic that is minimally restrictive and non-blocking. The simultaneous use of MES, SCADA, ERP and controllers synthesized by SCT requires the creation of an interface between them. This creation requires development time, delays the project, being inflexible to change and is subject to failure. One of the formal models for the synthesis of DES controllers in the SCT is the DFA (Deterministic Finite Automaton). DFA is one of the computational models within the theory of automata. This paper shows the use of the DFA models to build the DES controller to interface SCADA and MES to save development time and to deal with flexibility and failure-tolerant issues.